Grafts vs. flaps: a comparative study of Bracka repair and staged transverse preputial island flap urethroplasty for proximal hypospadias with severe ventral curvature - Zhang, Youtian; Wang, Xin; Wu, Yong; Li, Shengbin; Zhang, Dongzheng; Ma, Xiong; Wang, Cong; Zhang, Zhenhua; Ma, Yukun; Wei, Baolong; Guan, Yong (Frontiers in Pediatrics, 2023)
Introduction: Bracka repair and staged transverse preputial island flap urethroplasty are both significant methods in treating proximal hypospadias. They utilize the flap and graft techniques, respectively, to achieve a satisfactory success rate. This study aimed to compare the outcomes of these 2 methods in the treatment of proximal hypospadias with severe ventral curvature. Methods: We retrospectively analyzed 117 cases of proximal hypospadias with severe ventral curvature who had undergone either Bracka repair (n=62) or staged transverse preputial island flap urethroplasty (n=55). All operations were performed by a single surgeon, and the choice of method was determined by the surgeon’s preference based on his experience. Cosmetic outcome was evaluated with Pediatric Penile Perception Score (PPPS). Patients' characteristics including age, penis length, glans diameter, length of the urethral defect and ventral curvature degree, cosmetic outcomes, and complication rates were all compared. Results: There was no significant difference in age, penis length, glans diameter, length of the urethral defect, or ventral curvature degree. In the Bracka group, there were 5 patients with fistula, 1 patient with stricture, and 1 case of dehiscence. In the staged transverse preputial island flap urethroplasty group, there were 4 patients with fistula, 1 with stricture, and 2 with diverticulum. The scores of shaft skin and general appearance were consistently higher in the Bracka group than in the staged transverse preputial island flap urethroplasty group. The differences in complication rate and cosmetic outcome were not statistically different (P >0.05). Conclusions: Bracka repair and staged transverse preputial island flap urethroplasty are both satisfactory staged surgical options for proximal hypospadias with severe ventral curvature and have similar complication rates. Bracka repair may create a better appearance, but more studies are needed to confirm this finding. Pediatric surgeons should consider additional factors, such as the patient’s specific condition, parents’ inclination, and personal experience, rather than safety, to make the best choice between the 2 methods.